Effectiveness of face-to-face and webinar combination in increasing understanding on school wellbeing for elementary headmasters in Yogyakarta Special Region - Kartika Nur Fathiyah; Diana Setiyawati (Psychological Research and Intervention, 2018)
This research aims to determine the effectiveness of face-to-face and webinar combination in increasing elementary school headmasters’ comprehension on School Wellbeing in Yogyakarta Special Region.This study used a quasi-experimental design. The subject of the research is 29 elementary school headmasters across Yogyakarta Special Region (abbreviated as DIY) that have participated in pretest, initial face-to-face session, webinar sessions, final face-to-face session, and posttest. The data analysis used t-test analysis using SPSS version 21 to analyze School Wellbeing, pre and post training.The result of the research shows that the combination of face-to-face and webinar sessions is proven effective to increase the comprehension on School Wellbeing of elementary school headmasters across DIY. However, after being reviewed from the process, the training session needs to be revised considering that many of the participants did not follow the entire session due to the clashing of participants’ personal schedule and training session.